The effect of PET additive on mechanical and morphological properties of PP - Cavus, Fatma Kosovali; Ozcanli, Yesim; Beken, Murat (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
In this study, the mechanical and morphological properties of polypropylene (PP) / polyethylene terephthalate (PET) blends were investigated. The optimum ratio of the mechanical properties of PP / PET polymeric mixtures was determined accordingly. In order to determine the mechanical properties of the PP / PET blends, both dynamic mechanical analysis (DMA) and tensile tests were performed at a draw speed of 25 mm / min and at different ambient temperatures. In addition, it was analyzed by scanning electron microscopy (SEM) to observe the change of the morphological properties of PP/PET blends in relation to PET contribution. According to tensile test results, the highest Young's modulus and hardness values at room temperature were observed in PP + 40% PET sample. These results are supported by SEM results.
Keywords: polypropylene / polyethylene; tereplithalate blends; mechanical properties; morphological properties; POLYPROPYLENE; WASTE; Engineering